Implementasi Pemberdayaan Keluarga dalam Mencegah Kegawatdaruratan Stroke dengan Metode Face, Arms, Speech, Time (Fast) - Andrianur, Frana; Supriadi B., Supriadi B.; Parellangi, Andi; Rahman, Gajali; Setiadi, Rizky (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Stroke continues to increase which is a burden globally, the main prevention strategies are currently implemented but are not effective enough, so new prevention strategies will need which are expected to have a greater effect. Rapid recognition and reaction to signs of stroke and TIA is the concept of